PERANCANGAN DESAIN INTERIOR RESTORAN DELAGA BIRU, PORSEA, KABUPATEN TOBASA – SUMATERA UTARA - Damayantie, Irma (Universitas Esa Unggul, 2018)
AbstractPorsea area, Tobasa regency, North Sumatra is an area near Lake Toba which is currently still developed its tourism industry. One of the supporters of the tourism industry is in the restaurant business sector. A well-designed restaurant can be an attraction for visitors by not ruling out the food products it sells. Visitors to restaurants in the Delaga Biru tourist area can be visitors who live in homestay there and outside visitors who specifically come to this restaurant. The design of the restaurant will look as attractive as a tourism support facility in Porsea area, Tobasa regency. Design method used to arrange a development of facility supporting activity as tourist attraction of tourism. Method of completion data result comes from observation and reference of the work. While the application of data analysis method is using SWOT qualitative analysis to solve the problem of tourism design which supporting facilities in Porsea itself. Application of the concept of restaurant space applied to the segmentation of its natural tourism. As the result, space concept in designing interior of Delaga Biru restaurant theme is